Eosinophilic, Solid, and Cystic Renal Cell Carcinoma: Clinicopathologic Study of 16 Unique, Sporadic Neoplasms Occurring in Women. (January 2016) - Trpkov, Kiril; Hes, Ondrej; Bonert, Michael; Lopez, Jose I.; Bonsib, Stephen M.; Nesi, Gabriella; Comperat, Eva; Sibony, Mathilde; Berney, Daniel M.; Martinek, Petr; Bulimbasic, Stela; Suster, Saul; et al.
Abstract : A unique renal neoplasm characterized by eosinophilic cytoplasm and solid and cystic growth was recently reported in patients with tuberous sclerosis complex (TSC). We searched multiple institutional archives and consult files in an attempt to identify a sporadic counterpart. We identified 16 morphologically identical cases, all in women, without clinical features of TSC. The median age was 57 years (range, 31 to 75 y). Macroscopically, tumors were tan and had a solid and macrocystic (12) or only solid appearance (4). Average tumor size was 50 mm (median, 38.5 mm; range, 15 to 135 mm). Microscopically, the tumors showed solid areas admixed with variably sized macrocysts and microcysts that were lined by cells with a pronounced hobnail arrangement. The cells had voluminous eosinophilic cytoplasm with prominent granular cytoplasmic stippling and round to oval nuclei with prominent nucleoli. Scattered histiocytes and lymphocytes were invariably present. Thirteen of 16 patients were stage pT1; 2 were pT2, and 1 was pT3a. The cells demonstrated a distinct immunoprofile: nuclear PAX8 expression, predominant CK20-positive/CK7-negative phenotype, patchy AMACR staining, but no CD117 reactivity. Thirteen of 14 patients with follow-up were alive and without disease progression after 2 to 138 months (mean: 53 mo; median: 37.5 mo); 1 patient died of other causes. Although similar to a subset of renal cell carcinomas (RCCs) seen in TSC, we propose that sporadic "eosinophilic, solid, and cystic RCC, " which occurs predominantly in female individuals and is characterized by distinct morphologic features, predominant CK20-positive/CK7-negative immunophenotype, and indolent behavior, represents a novel subtype of RCC.